1999
DOI: 10.1136/ip.5.3.198
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive study of sledding injuries in Canadian children

Abstract: Objectives-(1) To describe the characteristics of sledding injuries presenting to a pediatric emergency department and (2) To describe the sledding environment that leads to childhood sledding injuries. Setting-A pediatric hospital emergency department in Ottawa, Canada and identified sledding sites in the region. Methods-All patients less than 18 years with sled related injuries were included. Questionnaires were completed gathering information on the sled operator, the sled, the sledding site, and the injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 18 publications
2
30
2
Order By: Relevance
“…The majority of previous studies reviewed cases from only one or a limited number of facilities that were often urban, referral hospitals or served a limited geographic area (Broder et al, 2005;Hartling et al, 1999;Lewis & Lasater, 1994;Ralis, 1981;Smith & Nelson, 1998). Overall hospitalization rate in our analysis (8%) was lower than the 18% reported in a tertiary-care-center study (Broder et al, 2005), and the sledding injury hospitalization rate (8%) was also lower than the 11%-15% observed in other studies (Lee et al, 1999;Major et al, 1999). In contrast, we discovered higher severity of injury compared with an occupational clinic study (Centers for Disease Control & Prevention, 1994); we identified 21% fractures and 61% superficial injury, sprains and strains versus 13% fractures and 87% less-severe injury in the occupational clinic setting.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…The majority of previous studies reviewed cases from only one or a limited number of facilities that were often urban, referral hospitals or served a limited geographic area (Broder et al, 2005;Hartling et al, 1999;Lewis & Lasater, 1994;Ralis, 1981;Smith & Nelson, 1998). Overall hospitalization rate in our analysis (8%) was lower than the 18% reported in a tertiary-care-center study (Broder et al, 2005), and the sledding injury hospitalization rate (8%) was also lower than the 11%-15% observed in other studies (Lee et al, 1999;Major et al, 1999). In contrast, we discovered higher severity of injury compared with an occupational clinic study (Centers for Disease Control & Prevention, 1994); we identified 21% fractures and 61% superficial injury, sprains and strains versus 13% fractures and 87% less-severe injury in the occupational clinic setting.…”
Section: Discussioncontrasting
confidence: 79%
“…Sledding on ice, as opposed to snow, can be particularly dangerous because higher speeds and limited steering while sliding on ice can lead to substantial injury from high-impact collisions with such immovable objects as trees, parked cars, or mailboxes (Lee et al, 1999;Major et al, 1999). Although MVCs can also cause serious injury, the high proportion of sprains and strains and relatively lower proportion of fractures or open wounds associated with MVCs in this evaluation imply that certain ice-related MVCs might have been relatively low-speed incidents from sliding on ice that can occur even when driving cautiously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with findings in other studies. 3,24 Such a high percentage of children sledding without supervision leads one to question whether sledding is another skill for which parental expectations may be inappropriate. Additional research is needed to address this question.…”
Section: Discussionmentioning
confidence: 98%
“…24 The most serious sledding injuries were incurred after the rider struck a tree or another stationary object in 60% and 76% of injuries. 25,26 Although the incidence of collisions with motor vehicles is low, these often have catastrophic consequences, 26,27 with head injury much more common. 28 Although many studies advocate helmet use for sledders, the efficacy of helmet use in sledding is uncertain, and there are no specific helmets designed for sledding.. Helmet use among sledders is significantly lower than for downhill skiing or snowboarding, with only about 3% of sledders wearing some form of head protection.…”
Section: Sledding/tobogganingmentioning
confidence: 99%